Coronarin D induces apoptotic cell death through the JNK pathway in human hepatocellular carcinoma. Issue 9 (3rd July 2018) - Lin, Hui‐Wen; Hsieh, Ming‐Ju; Yeh, Chao‐Bin; Hsueh, Kuan‐Chun; Hsieh, Yi‐Hsien; Yang, Shun‐Fa
Abstract: Coronarin D, a diterpene derived from the rhizomes of Hedychium coronarium, has been used to treat inflammatory diseases. Coronarin D can exert strong anticancer effects through cell growth prevention and cell cycle arrest in many cancer cells. In this study, we investigated the molecular mechanism through which coronarin D suppresses cell proliferation and triggers cell death in human hepatocellular carcinoma (HCC) cells. Treatment of Huh7 and Sk‐hep‐1 cells with coronarin D resulted in a significantly increased loss of mitochondrial membrane potential, leading to the cleavage and activation of caspase‐9, caspase‐8, and caspase‐3 and changes in Bax, Bcl‐2, and Bcl‐xL protein levels. Coronarin D significantly induced autophagy by increasing the expression of Beclin‐1 and LC3‐II and reducing the expression of p62. Moreover, Huh7 and Sk‐hep‐1 cells exposed to coronarin D had decreased expression of phosphorylated AKT, p38, and ERK and increased expression of phosphorylated JNK. Exposure of cells to the JNK‐specific inhibitor SP600125 attenuated the apoptotic effects of coronarin D. Taken together, this is the first study to report that coronarin D may effectively inhibit cell growth through apoptosis. We have provided evidence indicating that coronarin D induces cell death through the upregulation of JNK mitogen‐activated protein kinases in human HCC cells.